Factors causing delay of modification projects at Koeberg Power Station - Ntoyanto, Sikholiwe (Department of Construction Economics and Management, 2017)
Project delays are common in construction projects, and at Koeberg Nuclear Power Station, modification and outage projects are not exempted from these delays. Subsequently, these project delays have a detrimental effect on the Eskom organization in terms of its mandate to supply electricity to promote and boost the South African economy. Therefore, timely project delivery within the Eskom business is of paramount importance in ensuring the utility honours its mandate. The aim of this research study is to identify factors and that influence untimely delivery of plant system modification projects which at times affect the timely delivery of outage projects at Koeberg Power Station. The research study focuses on the following objectives: (i) identification of factors contributing to untimely delivery of plant system modification projects at Koeberg Power Station, (ii) analysis of identified factors to determine the main determinants of untimely delivery of plant system modification projects, (iii) assessing whether a gap or correlation exists between the factors identified through the study and the factors the project management fraternity believe to have a significant contribution to the untimely delivery of projects, and (iv) to recommend mitigating measures that Koeberg Power Station may consider in addressing the consequences of identified project delay factors on modification projects. Through the use of interactive management research methodology, a total of 92 identified project delay factors were reduced to 21 principal project delay factors that form part of the interpretive structural model. The results of the research study show that the main determinant of modification project delays at Koeberg Power Station is the "proficiency of a project manager". Proficiency of a project manager relates to the ability of a project manager to accomplish the required project tasks based on his or her skills, competency, and experience within the project management field. Inadequate proficiency of a project manager was found to be the major cause of modification delays at Koeberg Power Station. Proficiency of a project manager could not be directly matched with other project delay factors identified from the reviewed literature, but it could be matched with the "poor professional management" identified by Fugar and Agyakwah-Baah (2010). In addition, the matching of "proficiency of a project manager" project delay factor could also be established through other project delay factors identified by this study. These include poor leadership, competency, and skill of a project manager in communication, planning, coordination, risk management, and scope management. The study found that, a total of 9 out of 21 project delay factors identified are unique to Koeberg Power Station.